Reliability, safety, and security of railway systems : modelling, analysis, verification, and certification : second International Conference, RSSRail 2017, Pistoia, Italy, November 14-16, 2017, Proceedings /: modelling, analysis, verification, and certification : second International Conference, RSSRail 2017, Pistoia, Italy, November 14-16, 2017, Proceedings. (2017) - Unknown
No abstract available